The comparative study on factors affecting profitability for Malayan Banking Berhad and CIMB Bank Berhad / Nor Arshadah Abdul Kadr - Abdul Kadr, Nor Arshadah (2021)
The study aims to identify factors affecting bank profitability in Malaysia for Malayan Banking Berhad (MBB) and CIMB Bank Berhad (CIMB). The period of study is based on twenty-two (22) years of data from 1998 until 2019. Secondary data are obtained from reliable resources for studied variables. Dependent variables for profitability indicator are Return to Asset (ROA), Return to Equity (ROE) and Net Interest Margin (NIM). Independent variables are commonly categorized into Bank Specific variables, Industry Specific variable and Macroeconomic variables. This study has selected Return of Asset (ROA) as the dependent variable and focus on Capital Adequacy Ratio (CAR), Cost to Income (CTI), Gross Domestic Product (GDP) and Inflation (INF) as independent variables. Both Capital Adequacy Ratio (CAR) and Cost to Income (CTI) are Bank specific variables while Gross Domestic Product (GDP) and Inflation (INF) are Macro-economic variables. Malayan Banking Berhad (MBB) and CIMB Bank Berhad (CIMB) are chosen for being two leading banking institution in Malaysia and well established in many ASEAN countries. The relationship between variables is tested using Statistic / Econometric method. They are Test on Assumption (Normality test, Autocorrelation, Heteroscedasticity, Multicollinearity, RAMSEY), Descriptive analysis, Stationary test, Correlation analysis and Regression analysis (t-test, f-test, r square n etc.). The result is rather interesting for a discussion where only Gross Domestic Product (GDP) has a significant impact towards Return of Asset (ROA) for Malayan Banking Berhad while other variables are insignificant. As for CIMB Bank Berhad non of selected variables significantly related.